Examining the Use of Disciplinary Segregation within and across Prisons. (23rd February 2017) - Butler, H. Daniel; Steiner, Benjamin
Abstract : Prison officials have historically been afforded considerable discretion to administer sanctions designed to maintain order and security within a prison. Such discretion can generate disparate treatment of offender groups, but few studies have investigated whether sanction disparities exist within prisons, despite considerable research on sanctioning decisions made by other criminal justice actors. We use data collected from a nationally representative sample of inmates housed in state operated confinement facilities to examine potential influences of prison officials' decisions to impose one type of sanction—disciplinary segregation. Multi-level analyses reveal that both legally relevant criteria such as prior misconduct history and extralegal factors such as age and holding a prison job affected whether an inmate was placed in disciplinary segregation for a rule violation. Also, prisons in which a greater proportion of the inmate population is involved in prison work and prisons with a higher density of inmates classified minimum-security use disciplinary segregation less frequently.